Soil properties override climatic factors to shape soil nematode diversity in the eastern forest transect of China - Pang, Shuang; Hua, Bin; Yang, Wei; Zhang, Shuhan; Guan, Yupeng; Bai, Keyu; Fadda, Carlo; Mao, Rong; Zhang, Yang; Zhang, Ximei (Elsevier, 2024)
Soil nematodes are among the most significant soil-dwelling organisms in forest ecosystems. However, the factors that shape the distribution of soil nematodes are still not well explored. Therefore, we collected soil samples from 20 forest sites along the eastern transect of China and sequenced 18S rRNA V9 region to reveal the biodiversity of soil nematodes. Our study found that soil nematode richness is higher in temperate mixed needleleaf and broadleaf forests compared with the other four vegetation regions. Soil physiochemical properties overrode climatic factors to be the primary drivers of soil nematode richness and community composition. Importantly, the soil nematode richness significantly enhanced ecosystem multifunctionality, especially bacterial biomass and enzyme activities, with a determination coefficient (r2) of 0.23, suggesting that soil nematodes played essential roles in the forest ecosystem.